Transport and interaction of arsenic, chromium, and copper associated with CCA-treated wood in columns of sand and sand amended with peat - Hu, Ligang (2010)
Laboratory column leaching experiments were conducted to investigate the transport and interaction of As, Cr, and Cu associated with CCA-treated wood in sand with and without peat amendment. Results showed that leaching behavior of As, Cr, and Cu in these substrates were totally different. Substrate characteristics and microorganism activity posed distinct effects on the transport and transformation of these three elements. Arsenic was rapidly leached out from the columns with or without the amendment of peat, while Cr remained in all columns during the entire experimental period (215 days). Copper was leached out only in the substrate column without peat. The presence of microorganism clearly facilitated the transport of As, while it did not show obvious effects on the transport of Cr and Cu. Interactions among these three elements were observed during the processes of adsorption and transport. The adsorption of Cu on soil was enhanced with the adsorption of As, likely caused by a more negatively charged soil surface because of As adsorption. The adsorption of Cr on soil increased the adsorption of As due to the additional As binding sites induced by Cr adsorption. These results suggest that As concentrations in the soil affected by CCA-treated wood could largely exceed predictions based on soil adsorption capacity for As. The evaluation of the impact on human health associated with CCA-treated wood should take consideration of the distinct transport characteristics of three elements and their interactions in soils.